Habitat suitability modelling for Greater Kudu species using GIS and remote sensing technology in Gibe Sheleko National Park, southwestern Ethiopia - Kidist Sahle; Markato Markos (Cogent Food & Agriculture)
This study contributes to wildlife conservation in Gibe Sheleko National Park, southwestern Ethiopia, by employing advanced geospatial techniques, Geographic Information Systems (GIS) and Remote Sensing, to assess habitat suitability for the Greater Kudu (Tragelaphus strepsiceros). Although the park is rich in biodiversity, it lacks species-specific habitat suitability studies. We utilized Sentinel-2 satellite imagery, field data, and 30-year temperature averages (1992–2022). Six key environmental factors were considered: land use/land cover, elevation, temperature, and distances to rivers, roads, and settlements. The Analytic Hierarchy Process (AHP) was integrated with GIS to assign factor weights and evaluate their impact on habitat suitability. Results indicate that 48.28% (197.23 km²) of the park is highly suitable, 25.57% (104.47 km²) moderately suitable, 21.25% (86.80 km²) marginally suitable, 1.92% (7.83 km²) currently unsuitable, and 2.98% (12.19 km²) permanently unsuitable for the Greater Kudu. Although the area directly impacted by human activity is limited, settlements and agricultural expansion pose growing threats through habitat fragmentation. This study provides a valuable spatial decision-support tool, offering insight into the distribution of suitable habitats and guiding future conservation strategies. Immediate attention is required to manage human encroachment and ensure the long-term sustainability of the Greater Kudu population within the park.